USING RESINS AND OLSEN IN STUDYING PHOSPHORUS AVAILABILITY FOR CORN PLANTS IN CALCAREOUS SOIL IN THE NORTH OF IRAQ - Raida Ismail Abdalla Al-Hamdany (Mesopotamia Journal of Agriculture)
This study conducted at the field of the department of soil and water sciences /College of Agriculture and Forestry / Mosul University to study the effect of surface and sub – surface (15cm), soil using of nitrogen fertilizers Urea and Sheep manure and both in the presence and absence of sulphur on the available and P uptake by corn plants (Zea mays L.) . Urea and Sheep manure each alone or mixed with each at equal rate ( 80 kg N.D-1) and two levels of sulphur (Zero and 2.5 Ton D-1 ) before seeds corn (Zea mays v.106) planting which was done at Spring (April 1st) 2004.Available P was determind weekly,lasted for seven weeks,started from the 7th day of germination. The results indicated that addtion of both fertilizers (Urea and Sheep manure ) with sulfure significantly dominated over other treatments in the available and P uptake in both methods of application in all stages. Also available and uptake P significantly increased with time of fertilizers soil contact both methods of application. The sub – surface of urea and sheep manure with sulphur in the 7th week gave the highest amounte of available and uptake P.